Special volume, preface – 9th International Workshop on Astronomy and Relativistic Astrophysics: From Quarks to Cosmos. Issue 5 (13th June 2021) - Zen Vasconcellos, César A.; Hess, Peter O.; Piccinelli, Gabriella; Magaña, Mariana Vargas; Ureña‐Lopez, Luis; Felipe, Ricardo Gonzalez; Boller, Thomas; Gullberg, Steven
Abstract: This special volume includes contributions from some of the most relevant scientists who have participated in the IWARA 2020 Video Conference. The series of meetings known by the acronyms IWARA, STARS, and SMFNS, —more than a congregation of events, students and researchers which in itself would be extremely important for science—became in last years a kind of platform for scientific and academic projects, partnerships and presentation of high‐quality research contributions describing original and unpublished results on several topics related as new phenomena and new states of matter in the Universe, general relativity, gravitation, cosmology, astrophysics, particle and nuclear physics, and topics related. And the scientists participating in this volume, perfectly integrated with this design, bring more than just a glimpse into the technical toolbox of their work, be it theoretical or experimental. In addition to international scientific recognition, these researchers are mentors of students and young researchers, and demonstrate, in these contributions, also glimpses of systematically complex decisions made about the interpretation of data, about which problems are relevant to pursue, thus contributing a lot to the craft of science and its development.